PERAN SEKOLAH DAN KELUARGA DALAM MEMBENTUK KARAKTER RELIGIUS PESERTA DIDIK DI MTS UNGGULAN AL-QODIRI 1 JEMBER - Dea Monica Sary; Chalimatus Sa’dijah (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
Education is something essential for each person. Guardians are the principal madrasa who assume a vital part during the time spent person working in youngsters. Because children are the ultimate imitators and imitators, they will imitate what their parents do, and will also apply what their parents have taught them. The school environment also plays a role in the life and development of children's learning. Schools as spots of instruction should have the option to add to the arrangement of strict person in youngsters. In this examination, the scientist goes about as a key instrument, and the strategy utilized is the technique for perception, meetings and documentation. Also, the aftereffects of the examination acquired on the job of schools and families in molding the strict person of understudies are as teachers, good examples, directors, and counsels. And the value implanted is the value of hablum minallah, hablum minannas, and hablum minal 'alam. Kata Kunci: Peran, Sekolah, Keluarga, Karakter Religius